2019
DOI: 10.1002/jcc.26060
|View full text |Cite
|
Sign up to set email alerts
|

Water in Ras Superfamily Evolution

Abstract: The Ras GTPase superfamily of proteins coordinates a diverse set of cellular outcomes, including cell morphology, vesicle transport, and cell proliferation. Primary amino acid sequence analysis has identified Specificity determinant positions (SDPs) that drive diversified functions specific to the Ras, Rho, Rab, and Arf subfamilies (Rojas et al. 2012, J Cell Biol 196:189–201). The inclusion of water molecules in structural and functional adaptation is likely to be a major response to the selection pressures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…This reflects the hydration of the proteins by pressure, 3,6,8 as similarly observed in many high pressure crystal structures, 46–48 and may probably participate to the water-mediated allosteric interactions. 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reflects the hydration of the proteins by pressure, 3,6,8 as similarly observed in many high pressure crystal structures, 46–48 and may probably participate to the water-mediated allosteric interactions. 33 …”
Section: Resultsmentioning
confidence: 99%
“…This reflects the hydration of the proteins by pressure, 3,6,8 as similarly observed in many high pressure crystal structures, [46][47][48] and may probably participate to the watermediated allosteric interactions. 33 In all structures of Ras(wt) and Ras(D33K) under pressure, there is almost no structural modification in the P-loop which tightly binds to the phosphate groups and contains the crucial Lys 16 and Ser 17 residues, as well as in the G4 and G5 motifs, both connected to the purine moiety of the nucleotide. The intrinsic rigidity of these regions, revealed by pressure, is therefore directly connected to the Ras cycling efficiency.…”
Section: Crystal Structures Of Ras(wt) and Ras(d33k) Below And Above ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis also indicated that the switch regions are connected, with switch II driving the motion of switch I [49]. Conserved water molecules were also shown to be an integral part of Ras structure and catalysis [50,51].…”
Section: The Overall Ras Conformational Ensemblementioning
confidence: 93%
“…superfamily to be discovered, and then Ran, Rho, Rab, Arf and other families (Marcus and Mattos, 2020). They control different signal transduction pathways in cells, including proliferation, differentiation, morphology, polarity, adhesion, migration, survival, apoptosis, etc.…”
mentioning
confidence: 99%